Nicotine Increases Alcohol Intake in Adolescent Male Rats - Lárraga, Armando; Belluzzi, James D.; Leslie, Frances M. (Frontiers in Behavioral Neuroscience, 2017)
Background: Use of alcohol and tobacco, the two most concurrently abused drugs, typically first occurs during adolescence. Yet, there have been no systematic analyses of ethanol (EtOH) and nicotine (Nic) interactions during adolescence. Recent animal studies report that kappa-opioid (KOR) receptor activation mediates age differences in drug reinforcement. Our hypothesis is that concurrent self-administration of EtOH and Nic will be greater in adolescent rats because of age differences in KOR function. Furthermore, exposure to alcohol and nicotine during adolescence has been reported to increase EtOH intake in adulthood. We performed a longitudinal animal study and hypothesized adolescent rats allowed to self-administer nicotine would drink more alcohol as adults. Methods: Adolescent, postnatal day (P)32, and adult (P90) male and female Sprague-Dawley rats were allowed to self-administer EtOH, Nic, or a combination of both, EtOH+Nic, in an intravenous self-administration paradigm. The role of KOR was pharmacologically evaluated with the KOR antagonist, norbinaltorphamine (norBNI) and with the KOR agonist, U50,488H. Alcohol drinking was subsequently evaluated with male rats in a drinking in the dark (DID), 2-bottle choice test. Results: Concurrent Nic increased EtOH intake in adolescent males, but not in adults or females. Pharmacological blockade of KOR with norBNI robustly increased EtOH+Nic self-administration in adult male rats, but had no effect with female rats. Lastly, in our longitudinal study with male rats, we found prior self-administration of Nic or EtOH+Nic during adolescence increased subsequent oral EtOH intake, whereas prior self-administration of EtOH alone in adults increased subsequent EtOH drinking. Conclusions: There are major age- and sex-differences in the reinforcing effects of EtOH+Nic. Adolescent males are sensitive to the reinforcing interactions of the two drugs, whereas this effect is inhibited by KOR activation in male adults. Nicotine self-administration in adolescent males also increased subsequent oral EtOH intake. These findings suggest that brain mechanisms underlying the reinforcing effects of EtOH and nicotine are both age- and sex-dependent, and that tobacco or e-cigarette use may increase the vulnerability of teenage boys to alcohol abuse.